Anterior approach vs conventional hepatectomy for resection of colorectal liver metastasis: a randomized clinical trial - Rahbari, Nuh Nabi; Birgin, Emrullah; Bork, Ulrich; Mehrabi, Arianeb; Reißfelder, Christoph; Weitz, Jürgen (JAMA surgery, 2021)
Tumor relapse after partial hepatectomy for colorectal liver metastasis (CRLM) remains an unsolved issue. Intraoperative manipulation of the liver during conventional hepatectomy might enhance hematogenous tumor cell spread. The anterior approach is an alternative approach that may reduce intraoperative tumor cell dissemination.To determine the efficacy and safety of the anterior approach compared with conventional hepatectomy in patients undergoing resection for CRLM.This randomized clinical study evaluated the efficacy and safety of the anterior approach compared with conventional hepatectomy in adult patients with CRLM who were scheduled for hepatectomy from February 1, 2003, to March 31, 2012, at a tertiary-care hospital. A total of 80 patients with CRLM were randomized to the anterior approach and conventional hepatectomy groups in a 1:1 ratio. Bone marrow and blood samples were analyzed for disseminated tumor cells and circulating tumor cells (CTC) using cytokeratin 20 reverse transcriptase-polymerase chain reaction analysis. Data were analyzed from April 1 to December 1, 2018, using intention to treat.Anterior approach vs conventional hepatectomy.The primary end point was intraoperative CTC detection in central blood samples after liver resection. Secondary end points included postoperative morbidity, mortality, and long-term survival.Among the 80 patients included in the analysis (48 men [60%]; mean [SD] age, 61 [10] years), baseline characteristics, including preoperative CTC detection, were comparable between both groups. There was no statistically significant difference in intraoperative CTC detection between patients in the conventional hepatectomy (5 of 21 [24%]) and anterior approach (6 of 22 [27%]) groups (P > .99). Except for a longer operating time in the anterior approach group (mean [SD], 171 [53] vs 221 [53] minutes; P < .001), there were no significant differences in intraoperative and postoperative outcomes between both study groups. Although detection of CTC was associated with poor overall (median, 46 [95% CI, 40-52] vs 81 [95% CI, 54-107] months; P = .03) and disease-free (median, 40 [95% CI, 34-46] vs 60 [95% CI, 46-74] months; P = .04) survival, there was no significant difference in overall (median, 73 [95% CI, 42-104] vs 55 [95% CI, 35-75] months; P = .43) and disease-free (median, 48 [95% CI, 40-56] vs 40 [95% CI, 28-52] months; P = .88) survival between the conventional hepatectomy and anterior approach groups. Also, there was no significant difference in patterns of recurrence between both groups.This randomized clinical trial found that the anterior approach was not superior to conventional hepatectomy in reducing intraoperative tumor cell dissemination in patients undergoing resection of CRLM.isrctn.org Identifier: ISRCTN45066244
November 4, 2020
Gesehen am 14.02.2022